PENGEMBANGAN WADUK JATILUHUR SEBAGAI KAWASAN WISATA TERPADU KABUPATEN PURWAKARTA - Dwi Pratiwi Wulandari; Endah Trihayuningtyas; Wisi Wulandari (Rang Teknik Journal, 2021)
Waduk Jatiluhur is in Jatiluhur Subdistrict, Purwakarta Regency, West Java Province. Now Perum Jasa Tirta II as a manager has been developing Waduk Jatiluhur as an integrated tourism area through Tourism Division with the aim of improving development effectiveness. Based on the results of the study can be concluded that the main of supporting factors is the beautiful natural panorama, the extent of Waduk Jatiluhur area and the atmosphere of tourism objects that provide comfort for visitors. However, the pattern of land use in Waduk Jatiluhur area that is considered to have supported the tourism activities does not have a zoning system so that the activity of tourism and hydropower activities have not had a clear division of zones. In supporting the development of tourism in Waduk Jatiluhur, zoning area is needed to separate the core activities of the Dam River Basin and Hydroelectric Power Plant with tourism activities or with community ponds to avoid errors in the land use so that the development of tourism can provide maximal contribution.